THE RELATION OF THE STUDENTS OF PEDAGOGY'S COURSE WITH THE MATHEMATICAL KNOWLEDGE AND ITS TEACHING: A LONGITUDINAL STUDY - Ortega, E. M. [UNESP]; Santos, V. M. (Centro Federal Educacao Tecnologica Rio Grande Norte, 2018)
This essay is included in the field of Mathematic Education and of more direct way is related to formation of the teachers that teach Mathematic in the initial years of the Elementary Level. It is about analytical-descriptive lifting by longitudinal study, in the context of a qualitative approach. The study was done with students of the course of Pedagogy that began it at 2007 and the concluded at 2010. We present results about the relation of the students with the mathematical knowledge and its teaching during the period of initial formation. From texts produced by subjects of the research at the end of each year of the course of Pedagogy (2007, 2008, 2009 e 2010), we visualized changes in relation to mathematical knowledge and its teaching. These changes indicate that they finish the course closer of the mathematical knowledge, highlight the necessity of constant study about this field and there are ruptures of beliefs like those related to mathematics being inaccessible. We also realized worry of the subjects with the relation between teacher and students in the process of teaching and learning as well with the use of diversified activities, jokes, games, necessity of explaining the concepts in different ways, use of different didactic material, necessity of showing a importance of apply the mathematics concepts.
Keywords: Mathematical knowledge; Teaching of Mathematic; Pedagogy; Longitudinal Study